Chronic invasive sinus and intracerebral aspergillosis controlled by combination therapy with micafungin and a daily dose of 400 mg itraconazole oral solution. Issue 2 (February 2015) - Ogawa, Taku; Matsumoto, Kana; Tsujimoto, Kazunori; Hishiya, Naokuni; Yamada, Yutaka; Uno, Kenji; Kasahara, Kei; Maeda, Koichi; Nario, Kazuhiko; Mikasa, Keiichi; Morita, Kunihiko
Abstract Chronic invasive aspergillosis of the sinus is frequently fatal in the absence of early surgical and chemotherapeutic intervention because of its invasion of vascular tissue. We attempted to control a case of inoperable invasive aspergillosis of the sinus with micafungin and itraconazole oral solution. We prescribed a daily oral dose of 400 mg of itraconazole, which is twice the usual dose, and monitored the serum concentration of the drug. Finally, we were able to control the spread of the lesion. This case indicates that combination therapy with micafungin and a daily dose of 400 mg itraconazole oral solution is an alternative treatment strategy for inoperable invasive aspergillosis of the sinus.